Solo Leveling: Volume 3 - Chugong; Torres, J., 1969-; Im, Hye-Young; Blackman, Abigail; Chugong (2021)
Thus far, Jinwoo has managed to keep his rapid evolution hidden from his fellow hunters. When he arrives at his latest assignment, though, he is greeted by a group of familiar faces--Joohee, Mr. Song, and the other survivors of the double dungeon are gathered for the raid, and his comrades cant help but notice Jinwoos drastic change in stature! Jinwoo intends to act the weakling he was before, but when their party is joined by a group of criminals and their association minder, Jinwoo may have no choice but to push his newly acquired skills to the limit if he and his friends want to get out alive!
"Older teen, OT; LV"--Back cover
Keywords: Hunters -- Comic books, strips, etc; Monsters -- Comic books, strips, etc; Quests (Expeditions) -- Comic books, strips, etc; Magic -- Comic books, strips, etc; Imaginary wars and battles -- Comic books, strips, etc; Graphic novels; Adult Graphic novels